Towards A Generic Approach to Assessment in Adult And Continuing Education - David J. Jones (Adult Education Research Conference, 2000)
This paper offers a theoretical model for the assessment of student learning which centres on the nature of the evidence we use in order to carry out these assessments. It addresses questions of how we can identify what learning has taken place and what evidence is acceptable for such an identification.